2011
DOI: 10.1097/fch.0b013e318202a720
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Approaches to Community Health

Abstract: Poor people and people of color are more likely to live shorter and sicker lives and are less likely to survive a host of chronic illnesses. Policies and organizational practices that improve the environments in which people live, work, learn, and play can reduce these disparities. Using the World Health Organization's "Call to Action" principles as a discussion framework, we highlight the Centers for Disease Control and Prevention's Racial and Ethnic Approaches to Community Health programs that have developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The increase in chronic diseases in developing countries is consequent to the increasing prevalence of risk factors, such as increased alcohol consumption, smoking, obesity, physical inactivity and low fruit and vegetable intake. Poverty is closely linked with social determinants of chronic disease, such as poor education [ 14 ], ethnicity [ 15 ], age, poor diet and tobacco use [ 16 ]. In this report, a higher prevalence of hypertension in females was found compared with the PAHO/WHO National STEPS Survey.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in chronic diseases in developing countries is consequent to the increasing prevalence of risk factors, such as increased alcohol consumption, smoking, obesity, physical inactivity and low fruit and vegetable intake. Poverty is closely linked with social determinants of chronic disease, such as poor education [ 14 ], ethnicity [ 15 ], age, poor diet and tobacco use [ 16 ]. In this report, a higher prevalence of hypertension in females was found compared with the PAHO/WHO National STEPS Survey.…”
Section: Discussionmentioning
confidence: 99%
“…Cultural minorities are susceptible to experiencing difficulties in discriminatory environments, which may result in poor psychological well-being (Schmitt, Branscombe, Postmes, & Garcia, 2014). Past studies have shown that ethnic minorities in the United States were more likely to encounter racism (Buckner-Brown et al, 2011) and perceive higher levels of discrimination than European Americans (e.g., Miranda, Polanco-Roman, Tsypes, & Valderrama, 2013). However, in the face of racial discrimination, some people are able to cope better than others; in other words, how people react to adversity differs (Lee, 2005).…”
mentioning
confidence: 99%
“…In addition, the REACH US coalitions worked with partners to implement Complete Streets policies, which provide accommodations for motorists, bicyclists, pedestrians, and public transit users, 11 and to support infrastructure for physical activity, such as improving the walkability and safety of neighborhood streets. To increase the available opportunities to engage in physical activity, REACH US implemented a variety of worksite wellness policies 12 and revitalized the community environment to include more accessible recreational areas.…”
Section: Methodsmentioning
confidence: 99%